2012
DOI: 10.1556/aphysiol.99.2012.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Trunk position influences joint activation pattern and physical performance during vertical jumping

Abstract: Eight well-trained males carried out squat jump and countermovement jump with large (SJL and CMJL) and with small (SJS and CMJS) range of motion to study the influence of trunk position on joint recruitment pattern and jumping height. The main criteria in SJS and CMJS were to maintain trunk in near vertical position during execution. Joint angles, activation time, time at maximum joint velocity for ankle joint, knee joint and hip joint, vertical propulsion time and jumping height were determined using film ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…This is not in line with the original hypothesis, where it was postulated that JS would show correlations between CMJ at the hip joint. The lack of greater mechanical similarity between the hip and ankle could be explained from previous research establishing trunk inclination role on jumping performance (25,36). In particular, Vanrenterghem et al (36) showed when the trunk is held in a vertical position (as would be the case during a loaded jump squat), there is greater knee joint moment developed, whereas this decreases by 13% when trunk inclination is not restricted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not in line with the original hypothesis, where it was postulated that JS would show correlations between CMJ at the hip joint. The lack of greater mechanical similarity between the hip and ankle could be explained from previous research establishing trunk inclination role on jumping performance (25,36). In particular, Vanrenterghem et al (36) showed when the trunk is held in a vertical position (as would be the case during a loaded jump squat), there is greater knee joint moment developed, whereas this decreases by 13% when trunk inclination is not restricted.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Vanrenterghem et al (36) showed when the trunk is held in a vertical position (as would be the case during a loaded jump squat), there is greater knee joint moment developed, whereas this decreases by 13% when trunk inclination is not restricted. It would seem that during a JS at lighter loads (,25% 1RM) because of the position of the bar on the upper back, this increases the trunk angle reducing the demand at the hip joint compared with an unloaded CMJ, subsequently increasing the involvement of knee extension in vertical translation (25). Therefore, despite more traditional analysis highlighting similarity in movement patterns between CMJ and JS, further analysis indicates that JS may alter the loading at joints based on the added constraints of the loaded bar which limit trunk movement compared with a CMJ.…”
Section: Discussionmentioning
confidence: 99%
“…As contrasted with RJ, CMJ is characterized by large angular displacements of the hip, knee, and ankle joints and longer ground contact time [15]. Proper flexion of the trunk, hip and knee is necessary to establish a higher jump height in the descending phase of CMJ [24]. From the descending motion through the ascending motion, it is important that the trunk and leg extensors be activated in the coordinated sequence to produce the large force [24].…”
Section: Discussion ▼mentioning
confidence: 99%
“…Proper flexion of the trunk, hip and knee is necessary to establish a higher jump height in the descending phase of CMJ [24]. From the descending motion through the ascending motion, it is important that the trunk and leg extensors be activated in the coordinated sequence to produce the large force [24]. The previous study has reported that the transverse abdominis was activated earlier than the EO and RA during a standing long jump [29].…”
Section: Discussion ▼mentioning
confidence: 99%
See 1 more Smart Citation